2012
DOI: 10.1007/s11096-012-9652-0
|View full text |Cite
|
Sign up to set email alerts
|

Storage and disposal of unused medications: knowledge, behavior, and attitudes among Serbian people

Abstract: Public services in Serbia, including government and health sectors, need to be more proactive about educating people on how to store and dispose medications, as well as finding a way for implementation of the law on medications wastage destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 19 publications
8
61
2
4
Order By: Relevance
“…Similar studies were done in Serbia and New Zealand Kusturica et al 2012;Seehusen & Edwards 2006) and their methods were considered and some parts of the questionnaire were utilised in this study. The author agreed for their questionnaire to be reproduced and used.…”
Section: Methodsmentioning
confidence: 99%
“…Similar studies were done in Serbia and New Zealand Kusturica et al 2012;Seehusen & Edwards 2006) and their methods were considered and some parts of the questionnaire were utilised in this study. The author agreed for their questionnaire to be reproduced and used.…”
Section: Methodsmentioning
confidence: 99%
“…Several international studies have shown that 48-75% of their population are aware that improper disposal of unwanted medication will lead to contamination of the environment. [9][10][11][12] The most common way to discard unwanted medication in majority of the countries is to throw it into the trash, [13][14][15][16] except for the Swedish where returning to the pharmacy is the predominant method to "dispose" unused medication. [17] A systematic review reported that due to the paucity of evidence, connection between knowledge on environment impact of inappropriate disposal and the preference toward disposal method cannot be established.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, accidental intake by children or elderly could be dangerous. [6] Indiscriminate disposal of garbage and sewage system can eventually release these harmful chemicals into the water supply which can adversely affect our health and environment in the long run. [7][8][9] In developing countries like India where accessibility of health insurance is scarce, medicine financing is mainly outof-pocket.…”
mentioning
confidence: 99%